ANALISIS RISIKO PRODUKSI PADA USAHATANI TOMAT DI DESA TAWANGARGO KECAMATAN KARANGPLOSO KABUPATEN MALANG - Mahmudah Mahmudah; Masyhuri Mahfudz; Sri Hindarti (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
AbstractThis research aims to determine the level of production risk and the factors that influence the risk of production in tomato farming in Tawangargo Village, Karangploso District, Malang Regency. This research was conducted intentionally in Tawangargo Village, Karangploso District, Malang Regency. Sampling using purposive sampling method with a number of samples taken amounted to 30 people. The data analysis method used is the Cobb-Douglas production function model to look at production risk factors and variation coefficient (CV) to see the level of production risk. The results of this research indicate that CV production risk is 12.8% which means the risk level is low and farmers avoid losses with a lower limit (L) of 39,547.24 Kg. Production risk factors that have a significant effect on tomato production are pesticides and labor.Keyword : risk, production, profit